Integration of Science and Religion: Salat Time in Astronomical Perspectives - Prastyorini*, Niken; Rofiuddin, Ahmad Adib (Universitas Syiah Kuala, 2024)
The integration between science and religion in determining prayer times is one of the efforts of astronomers to understand the Qur'an and at the same time deepen scientific knowledge. This makes Muslims aware of the importance of studying religious knowledge and general knowledge at the same time. This research is library research. By using references from previous studies, this study covers how prayer times are from an astronomical perspective. Determination of prayer times from an astronomical perspective always pays attention to the star's arguments that have been determined. The explanation of prayer times in the Qur'an and hadith needs to be redefined through the science of astronomy so that the integration between sciences can be clearly described.